A predictive model of waterpipe smoking cessation among women in southern Iran: application of the theory of planned behavior - Sara Dadipoor; Gholamreza Heydari; Niveen ME Abu-Rmeileh; Shokrollah Mohseni; Hadi Eshaghi Sani Kakhaki; Teamur Aghamolaei; Nahid Shahabi (BMC, 2023)
Abstract Background Today, waterpipe (WT) smoking is a rising issue worldwide, and has taken a significant and growing share of tobacco consumption in the world. Present study aimed to explore the predictors of WT cessation in the light of the theory of planned behavior (TPB). Methods This cross-sectional analytical study was conducted in 2021-2022 using a multi-stratified cluster sampling on 1,764 women in Bandar Abbas, southern Iran. Data were collected through a reliable and valid questionnaire. The three-part questionnaire includes demographic information, behavioral information of WT smoking, and the constructs of the TPB along with an additional habit construct. Multivariate logistic regression analysis was run to model the predictor constructs of WT smoking. The data were analyzed statistically in STATA14.2. Results With an increase in one attitude score, the odds of cessation increased by 31% (p < 0.001). Also, with an increase of one score in knowledge, the odds of cessation are increased by 0.05% (0.008). With an increase of one score for intention, the odds of cessation are 26% (0.000). in social norms, the odds of cessation are 0.02% (0.001). With an increase of one score in perceived control, the odds of cessation increased by 16% (0.000) and inhabit score, the odds of cessation decrease by 37% (0.000). In the model where the habit construct was present, the accuracy, sensitivity, and pseudo R2 indices were 95.69%, 77.31%, and 65%, respectively and after removing the habit construct, the so-called indices changed to 90.7%, 50.38% and 0.44%, respectively. Conclusions The present research confirmed the effectiveness of the TPB model in predicting waterpipe cessation behavior. The knowledge obtained from this research can help develop a systematic and effective intervention to facilitate waterpipe cessation. Focusing on the habit variable can play a critical role in waterpipe cessation in women.